PENGARUH RASIO MOLAR BUTANOL PADA UREA FORMALDEHIDE TERBUTILASI TERHADAP KARAKTERISTIK MATERIAL - Mukasi Wahyu K; Rochmadi _; Rochim Bakti C (PROSIDING SNAST, 2018)
Alkyd resin is a polymer product mostly used in paint, coating, and film making industries. This is due to the superiority of its properties as a surface coating such as flexibility, strength and durability, and adhesivity. This study made alkyd resin palm fatty acid distillate based (PFAD) and urea formaldehide butilated with variation of molar ratio of butanol 0.5-3 mgrek / mgrek. The result of residual hydroxyl from each variation is 1,25- 11,95 mgrek/g sampel. The more mole ratio of butanol the more difficult it becomes to polymer. Alkyd resin is then reacted with urea formaldehide butilated using oxalic acid catalyst. The result of the density test was obtained on the variation of 1: 0,5 and 1: 1 urea formaldehide butilated ratio with the ratio of alkyd resin and 1: 1 and 1: 2 urea formaldehide butilated with catalyst. Results obtained in the ratio of 1: 0,5 urea formaldehide butilated with 2: 1%mass alkyd resin ratio of curing time at 1.67 hours and 1: 1% mass curing time of 4.83 hours. As for the comparison of 1: 1 urea formaldehide butilated reacted with alkyd resin 2: 1% mass ratio obtained curing time of 6.43 hours and 1: 1% mass of 9.41 hours. More and more urea formaldehide butilated is used and using a catalyst to make the coating material drier faster.